Corrections and additions to the dating of the “Histoire Naturelle des Vers” and the Tableau Encyclopédie (Vers, coquilles, mollusques et polypiers) portions of the Encyclopédie Méthodique - Evenhuis, Neal L.; Petit, Richard E. (Zootaxa, 2003)
A recently published collation of the entire Encyclopédie Méthodique contained some errors in the Histoire Naturelle des Vers and the Tableau Encyclopédie (Vers, coquilles, mollusques et polypiers) portions. Those errors are here corrected and a few additional notes added.